E Evaluasi dan Uji Aktivitas Formulasi Sediaan Peel-Off Mask Anti Jerawat Ekstrak Batang Brotowali (Tinospora crispa L.) : Evaluasi dan Uji Aktivitas Formulasi Sediaan Peel-Off Mask Anti Jerawat Ekstrak Batang Brotowali (Tinospora crispa L.) - Amelia, Norrahmi; Malahayati, Siti; Melviani, Melviani; Noval, Noval (LPPM Universitas Sari Mulia, 2023)
Background: Facial skin care for acne treatment is better formulated in topical form, this is due to the duration of the active substances that interact with the skin. One dosage form is a peel-off mask with active substances brotowali stems which contain flavanoids, tannins, alkaloids as antibacterial causes acne. Objective: Analyzing the effect of variations in the concentration of brotowali stem extract (Tinospora crispa L.) on physicochemical evaluation and antibacterial activity of optimal anti-acne peel-off mask preparation formulations Methods: The research method used is True Experimental with a posttest only control group design research design. Make peel-off mask formulations with variations in extract concentrations of 20%, 30%, and 40%. The evaluation then includes organoleptis, homogeneity, dispersion, adhesion, dry time, pH, viscosity, and antibacterial activity tests, statistically analyzed using One Way ANOVA Results: Qualify in the organoleptis test is formula II (30%) and III (40%), the dispersion test is formula I (20%) and II (30%) with a p-value of 0.022, the adhesion test of all formulations with a p-value of 0.014, the dry time test of all formulations with a p-value of 0.000, the pH test is formula I (20%) with a p-value of 0.000, the viscosity test is formula II (30%) with a p-value of 0.000. The diameter of the formula's third inhibitory zone against propionibacterium acnes was 8.61mm ± 0.19 respectively; 14.31mm ± 3.88, and 15.54mm ± 4.80 with a p-value of 0.012 Conclusion: Variations on concentration of brotowali stem extract have an influence on physicochemical evaluation and antibacterial activity, the most optimal formulation is formulation II (30%)